Characterization of biofiber breakage in composite processing using a capillary rheometer. (August 2014) - Quijano-Solis, C; Yan, N
This study used a capillary rheometer to determine the impact that shear and elongational flow have on the breakage of aspen fibers in a polypropylene matrix. Composites were processed at different concentrations, temperatures, and rates of strain. The influence of the processing parameters was also analyzed. The difference in breakage of the fibers was assessed through their weight–average fiber length. Results showed that both types of flow exert influence on the total breakage of the fibers. In some cases, the percentage of breakage in the elongational flow is higher. The level of fiber breakage was similar for all fiber concentrations and shear rates. Temperature influence depended on the type of flow.